FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN WISATAWAN TERHADAP PRODUK OLEH-OLEH KHAS AMBON - Wattimena, Roy Alan (P3M Politeknik Negeri Ambon, 2022)
The tourism sector has a multiplier impact on various sectors and one that is inseparable is shopping activities carried out by tourists. Typical souvenir products are products that tourists always look for and buy when traveling somewhere because this behavior is an activity that often occurs. The purpose of this study is to analyze the factors that influence tourist satisfaction in shopping for typical souvenir products. The research method used is explanatory research with a survey approach. This study seeks to explain the causal relationship between variables and their effects through hypothesis testing. To test the hypothesis, each variable is measured with an instrument in the form of a questionnaire. Tests were carried out using multiple regression analysis (multiple regression analysis) and analyzed jointly for 125 respondents. This research is limited to examining the relationship between marketing mix elements of typical souvenir products and their effect on tourist satisfaction. While the typical souvenir products studied were limited to typical Ambon handicraft products The results of the analysis show that only two elements of the marketing mix affect tourist satisfaction, namely product and promotion. The implication of this research is that managers or sellers of typical Ambon souvenir products need to emphasize the importance of maintaining the uniqueness and quality of the product considering that tourists still emphasize tangible product forms.